Dissolved Nitrous Oxide and Hydroxylamine in the South Yellow Sea and the East China Sea During Early Spring: Distribution, Production, and Emissions - Gu, Xueji; Cheng, Fang; Chen, Xiaolei; Du, Guanxiang; Zhang, Guiling (Frontiers in Marine Science, 2021)
Coastal marine systems are active regions for the production and emission of nitrous oxide (N2O), a potent greenhouse gas. Due to the inherently high variability in different coastal biogeochemical cycles, the factors and mechanisms regulating coastal N2O cycling remain poorly understood. Hydroxylamine (NH2OH), a potential precursor of N2O, has received less attention than other compounds in the coastal areas. Here, we present the spatial distribution of N2O and the first reported NH2OH distribution in the South Yellow Sea (SYS) and the East China Sea (ECS) between March and April 2017. The surface N2O concentrations in the SYS and the ECS varied from 5.9 to 11.3 nmol L–1 (average of 8.4 ± 1.4 nmol L–1) and were characterized by offshore and north–south decreasing gradients. NH2OH showed patchy characteristics and was highly variable, fluctuating between undetectable to 16.4 nmol L–1. We found no apparent covariation between N2O and NH2OH, suggesting the NH2OH pathway, i.e., nitrification (ammonium oxidation), was not the only process affecting N2O production here. The high NH2OH values co-occurred with the greatest chlorophyll-a and oxygen levels in the nearshore region, along with the relationships between NO2–, NO3–, and NH2OH, indicating that a “fresh” nitrifying system, favoring the production and accumulation of NH2OH, was established during the phytoplankton bloom. The high N2O concentrations were not observed in the nearshore. Based on the correlations of the excess N2O (ΔN2O) and apparent oxygen utilization, as well as ΔN2O vs. NO3–, we concluded that the N2O on the continental shelf was mainly derived from nitrification and nitrifier denitrification. Sea-to-air fluxes of N2O varied from −12.4 to 6.6 μmol m–2 d–1 (−3.8 ± 3.7 μmol m–2 d–1) using the Nightingale et al. (2000) formula and −13.3 to 6.9 μmol m–2 d–1 (−3.9 ± 3.9 μmol m–2 d–1) using the Wanninkhof (2014) formula, which corresponds to 75–112% in saturation, suggesting that the SYS and the ECS acted overall as a sink of atmospheric N2O in early spring, with the strength weakening. Our results reveal the factors and potential mechanisms controlling the production and accumulation of NH2OH and N2O in the SYS and the ECS during early spring.